Efektivitas Penggunaan Media Promosi Kesehatan Video dan Ceramah terhadap Tingkat Pengetahuan tentang Anemia pada Siswi di SMPN 19 Kota Tasikmalaya - Rosmala, Fenty (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
Anemia is a condition where the hemoglobin level or red blood cell count is below normal, which varies depending on the age and condition of the individual. Its prevalence is high in developing countries, including Indonesia, especially in adolescent girls. Iron deficiency is one of the main factors. Adolescent girls who are anemic are at greater risk of developing anemia during pregnancy, which can interfere with fetal growth and increase the risk of delivery complications. Education through health promotion media is needed to improve knowledge, including through videos and lectures. Videos present information in an interesting audiovisual manner, while lectures convey information orally directly to the audience. This study aims to determine the effectiveness of video and lecture media on increasing knowledge about anemia in female students of SMPN 19 Tasikmalaya City. The method used was true experiment with pretest-posttest design with control group. The sample amounted to 64 students, divided into two groups: video media (32 students) and lectures (32 students). Statistical test results showed a significance value of 0.041 in the video group and 0.000 in the lecture group (p < 0.05). It can be concluded that both are effective in increasing knowledge, but lecture media is more effective than video.